Enabling informed policymaking for chronic kidney disease with a registry: Initiatory steps in Iran and the path forward. Issue 1 (March 2018) - Niazkhani, Zahra; Cheshmekaboodi, Mojgan; Pirnejad, Habibollah; Makhdoomi, Khadijeh; Nikibakhsh, Ahmad Ali; Abkhiz, Saeed; Mivefroshan, Azam; Jafari, Laleh; Zeynali, Javad; Mahmoodzadeh, Hashem; Afshari, Ali Taghizadeh; Bal, Roland
Abstract: Objectives: Chronic kidney disease (CKD) registries have been used for more than half a century. Iran lacks a comprehensive registry to capture data of all CKD patients for an informed care planning and policy making. We aimed to identify the objectives and possible challenges for developing a CKD registry and also to define its minimum data set (MDS) in our healthcare context. Methods: This was a mixed-method study conducted in Iran from fall 2016 till summer 2017. The qualitative part included document analysis and 26 semi-structured interviews with 17 clinicians and managers involved in CKD care. This data was analyzed using the "grounded theory". Then, a modified Delphi survey was conducted. Percentages and mode values were used for analysis. Results: Our participants' leading interest in a CKD registry was centered on providing a coordinated, good-quality care for all CKD stages with particular emphasis to capture events and monitor trends for patients in earlier stages. They highlighted the required financial, technical and human resources as main challenges for a smooth registry implementation. Furthermore, a clinically oriented MDS comprising of 168 elements (with a majority having more than 90% agreement with mode 2) was extracted. It mainly collects demographics, medical history, encounter sessions, diagnostic examinations, medications, vaccinations and mortality data. Conclusions: We reported the initiatory steps taken to establish a CKD registry in an Iranian healthcare context. We focused on the information needs and priorities of our main stakeholders and based our intended registry on addressing those needs. We hope this approach will facilitate its endorsement and advance the efforts for a sustainable, good-quality CKD care. Highlights: Disease registries provide reliable data planning and policymaking of chronic care Registry data particularly on earlier CKD stages is crucial for informed policy making Securing adequate financial, technical and human resources is a challenge for registries In a developing setting, a clinician supported registry MDS can ease its initial implementation